Experiência no ensino remoto de sequência didática na abordagem do tema sustentabilidade ambiental para alunos da terceira série do ensino médio de uma escola pública - Albuquerque, Márcio Valério Lins de (2022)
The theme Environmental Sustainability has been addressed in textbooks, in ecology content, in a superficial way, not being the theme contextualized by biology teachers. In this context, we developed a Didactic Sequence (DS) to address Environmental Sustainability, encouraging the engagement of students in the search for solutions to local environmental problems, promoting an investigative character in the construction of knowledge. The research was carried out with students from the 3rd grade of high school classes at the Deputado Antônio Cabral School, located in the neighborhood of Valentina Figueiredo, in João Pessoa, Paraíba. An DS containing four stages (three remote stages and a hybrid stage) addressed environmental Sustainability. In the first stage, an online tool (Padlet) was used to investigate students' perceptions of Environmental Sustainability. In the second stage, a directed study was carried out with a focus on the textbook. In the third stage, students researched other sources (articles and websites). In the fourth stage, the students were asked about environmental sustainability at the school, carried out in loco observations and exposed them to the school community. The results showed that at the beginning of the DS 67.9% of words, phrases, referring to the students‟ perceptions, were related and contextualized with Environmental Sustainability, and 32.1% were distant from the theme and/or were not contextualized. In the in loco observations at the school, the students identified situations and suggested actions to be adopted aiming at environmental sustainability. The students presented to the school community (students from other classes and teachers) their research, observations, reflections and suggestions for actions to be adopted such as recycling, planting a vegetable garden, reducing energy waste and awareness campaigns. At the end of the DS, 72.7% of words and phrases were related and contextualized with Environmental Sustainability and only 27.3% were distant from the theme or were not contextualized. The results showed that research-based learning stimulated communication, argumentation and problem solving in students. A manual of sustainable practices was produced, containing interactive activities, as an instrument to support the development of Didactic Sequences, helping in the teaching-learning process.